Lord of The Crowns: A New Precious in the Kingdom of Clustomesogens. (6th August 2018) - Guy, Kevin; Ehni, Philipp; Paofai, Serge; Forschner, Robert; Roiland, Claire; Amela‐Cortes, Maria; Cordier, Stéphane; Laschat, Sabine; Molard, Yann
Abstract: Replacing pure inorganic materials by functional organic–inorganic hybrid ones to lower production costs has become a major challenge, in particular for the optoelectronic industry. Adding nanostructuration abilities meanwhile preserving homogeneity is even more challenging for this class of new materials. Here we show that red‐NIR emissive ternary molybdenum cluster salts can be assembled to liquid crystalline 15C5 crown ethers. The resulting hybrids are homogeneous and stable up to high temperature despite the weakness of the supramolecular interactions binding both components. These are illustrated by 133 Cs MAS NMR. All hybrids show hexagonal columnar arrangements and strong red‐NIR emission. Surprisingly, when chlorinated clusters are used instead of brominated ones, the mesophase stability is largely enhanced.